Discovery of a Novel Long Noncoding RNA Lx8-SINE B2 as a Marker of Pluripotency. (8th February 2021) - Chen, Fuquan; Zhang, Miao; Feng, Xiao; Li, Xiaomin; Sun, Haotian; Lu, Xinyi
Abstract : Pluripotency and self-renewal of embryonic stem cells (ESCs) are marked by core transcription regulators such as Oct4, Sox2, and Nanog. Another important marker of pluripotency is the long noncoding RNA (lncRNA). Here, we ind that a novel long noncoding RNA (lncRNA) Lx8-SINE B2 is a marker of pluripotency. LncRNA Lx8-SINE B2 is enriched in ESCs and downregulated during ESC differentiation. By rapid amplification of cDNA ends, we identified the full-length sequence of lncRNA Lx8-SINE B2 . We further showed that transposable elements at upstream of lncRNA Lx8-SINE B2 could drive the expression of lncRNA Lx8-SINE B2 . Furthermore, ESC-specific expression of lncRNA Lx8-SINE B2 was driven by Oct4 and Sox2. In summary, we identified a novel marker lncRNA of ESCs, which is driven by core pluripotency regulators.